Cutting-Edge Approaches in the Co-Amorphization Process - Azza A. K. Mahmoud; Géza Regdon; Katalin Kristó (Pharmaceutics)
Background: Recently, the co-amorphization method has been widely used to refine the bioavailability characteristics of poorly soluble drugs in addition to overcoming the drawbacks of other traditional amorphization techniques. Objectives: The main aim of this systematic review is to present an extensive outline of different co-former classes, co-former selection, and evaluation of produced co-amorphous systems. Methods: The systematic research was carried out based on three different databases, including PubMed, Scopus, and Web of Science time using co-amorphous, co-former, and drug as keywords. The selected papers were written in the English language and published between 2016 and 2024, and they focused on the co-amorphous systems, while articles discussing other amorphization techniques and crystallization processes were excluded. Results: 127 peer-reviewed articles were selected and summarized. Conclusions: This paper revealed that amino acid is the most commonly used co-former, specifically arginine with acidic drugs and tryptophan with acidic and basic drugs, and it reported other co-formers that were used and different co-amorphous systems with their dissolution behaviour and stabilities, and different computational tools that were applied in the selection of co-former and process result evaluation.